A fig deal: A global look at fig mosaic disease and its putative associates. - Preising, Stephanie; Borges, Darlan; de Queiroz Ambrósio, Márcia Michelle; da Silva, Washington L. (Plant disease, 2021)
16 citations (Crossref) [2023-10-31]
Keywords: Badnavirus; Connecticut; Ficus; Phylogeny; Plant Diseases; dept.bio; peer-reviewed; phylogeny; plant disease

Detection of multiple grapevine viruses in New England vineyards - Borges, Darlan Ferreira; Preising, Stephanie; de Queiroz Ambrósio, Márcia Michelle; da Silva, Washington Luis (Crop Protection, 2020)
Vineyards in the New England region of the USA were surveyed for the occurrence of grapevine viruses. A total of ten vineyards were visited and 62 composite samples of leaves with the petioles were collected from symptomatic grapevines (Vitis spp.). All of the samples were assayed by double-antibody sandwich enzyme-linked immunosorbent assays (DAS-ELISA) using antibodies specific for four major grapevine leafroll-associated viruses (GLRaV-1, GLRaV-2, GLRaV-3, and GLRaV-4), grapevine fanleaf virus (GFLV), tobacco ringspot virus (TRSV), and tomato ringspot virus (ToRSV). Positive ELISA samples were further tested by reverse transcription polymerase chain reaction (RT-PCR) with primers specific for each of the viruses to confirm the ELISA results. Twenty-two samples were infected with at least one of the viruses tested. GLRaV-3 (24.19%) was the most prevalent virus detected followed by GLRaV-1 (12.90%), ToRSV (3.23%), and GLRaV-2 and TRSV (1.61%). This is the first study reporting on the presence of grapevine viruses in New England. Extensive surveys need to be conducted to evaluate the prevalence and economic impact of these viruses on New England vineyards. © 2020 Elsevier Ltd
5 citations (Crossref) [2023-10-31] tex.ids: borgesDetectionMultipleGrapevine2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85081269363 type: Article
Keywords: Grapevine fanleaf virus; Grapevine leafroll-associated virus 1; Grapevine leafroll-associated virus 3; Grapevine viruses; New England; Tobacco ringspot virus; Tomato ringspot virus; United States; Vineyards; Vitis; dept.bio; detection method; economic impact; pathogen; peer-reviewed; tobacco; vineyard; viral disease; virus

Gathered from the Vine: A Survey of Seven Grapevine Viruses Within New England Vineyards - Dumas, Madeleine; Borges, Darlan Ferreira; Priesing, Stephanie; Tippett, Ethan; Ambrosio, Márcia Michelle de Queiroz; Luís da Silva, Washington (Plant Disease, 2023)
Vineyards in the Southeastern New England American Viticultural Area were surveyed for the incidence of seven major viruses: grapevine leafroll-associated viruses (GLRaV-1, GLRaV-2, GLRaV-3, and GLRaV-4), grapevine fanleaf virus (GFLV), tomato ringspot virus (ToRSV), and tobacco ringspot virus (TRSV). Viruses were detected by DAS-ELISA and confirmed by RT-PCR and Sanger sequencing. Multiple viruses were present in 19 out of the 25 vineyards surveyed between 2018 and 2020. GLRaV-3 (27.59%) was the most prevalent virus followed by GLRaV-4 (14.90%), GLRaV-1 (13.52%), GLRaV-2 (11.03%), ToRSV (6.34%), GFLV (5.24%), and TRSV (2.62%). Furthermore, phylogenetic analyses of the viral partial genome sequences acquired in this study revealed that the grapevine viruses present in this area are diverse, indicating that they may have been introduced from different sources. Our findings stress the need for improving the sanitary status of planting materials to avoid the introduction and dissemination of viruses to vineyards in this important wine-producing region of New England.
0 citations (Crossref) [2023-10-31]
Keywords: New England; dept.bio; grapevine fanleaf virus; grapevine leafroll-associated virus; grapevine viruses; peer-reviewed; survey; tobacco ringspot virus; tomato ringspot virus

Lignin-derived carbon dots from leaf waste as sustainable plant sunscreens and UV-protective foliar coatings - Thangavelu, Raja; Gray, Sarah; Wu, Binlin; Pellegrino, Richard; da Silva, Washington; Zuverza-Mena, Nubia; Dimkpa, Christian; White, Jason (Environmental Science Nano, 2026)
Keywords: Agricultural waste; Agriculture; Carbon fibers; Lignin; Maple; Sustainable agriculture; Sustainable production; dept.phy